Ultrathin eggshell type high-dispersion catalyst as well as preparation method and application thereof

By regulating the oxygen-containing groups on the surface of the alumina support, using heat treatment, crystallization and radiation, the problem of agglomeration or aggregation of active metals in eggshell catalysts is solved, and the high dispersion state and catalytic performance of active metals are improved.

CN119857480AActive Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311359592.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

In the prior art, when preparing eggshell catalysts, active metals are prone to agglomeration or aggregation, resulting in a decrease in metal dispersion and utilization rate and poor catalytic performance.

Method used

By regulating the surface properties of the carrier, using heat treatment, crystallization and radiation to treat alumina precursor mixtures containing carbon compounds, enriching and improving the type and density of oxygen-containing groups on the surface of the alumina carrier, and achieving a high dispersion state of the active metal in the extremely thin shell layer on the surface of the carrier.

Benefits of technology

The highly dispersed state of the active metal in the extremely thin shell layer on the support surface is achieved, which significantly improves the catalytic performance of the catalyst, especially in the selection of hydrogenation catalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857480A_ABST
    Figure CN119857480A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and particularly relates to an ultrathin eggshell type high-dispersion selective hydrogenation catalyst as well as a preparation method and application thereof. The eggshell-shaped catalyst comprises a carrier and active metal elements, the thickness is calculated from the outer surface of the carrier to the center, and the active metal elements accounting for 95-99 wt% of the total weight of the active metal elements are distributed in a shell, with the thickness within 60 microns, of the carrier and distributed in an eggshell shape; the dispersity of the active metal element is 50%-80%; the active metal elements comprise main metal elements and optional auxiliary metal elements. The active metal in the catalyst is distributed in an extremely thin shell layer area on the surface of the carrier and is in a highly dispersed state, and the catalyst shows excellent performance in a selective hydrogenation catalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to an ultra-thin eggshell-type highly dispersed selective hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Supported catalysts with metals as active components are widely used in the field of petrochemicals. According to the different enrichment sites of the active components, they can generally be divided into four forms: uniform, eggshell, yolk, and egg white. For noble metal supported catalysts, due to the scarcity and high price of noble metal resources, appropriate methods need to be used to enrich the noble metals on the surface of the carrier to form eggshell catalysts to improve the utilization rate of the noble metals, and the thinner the shell, the more conducive to surface fast reaction and diffusion-controlled catalytic reactions. However, it is generally believed that active metals are very easy to agglomerate or aggregate during the preparation of eggshell catalysts, resulting in a decrease in metal dispersion and utilization, and poor catalytic performance. Therefore, how to control the enrichment of active metals in the thin shell of the carrier while maintaining their uniform distribution under the premise of keeping the total amount of active metals unchanged is a current research hotspot and difficulty.

[0003] CN101730588A discloses a catalyst for selective hydrogenation of alkynes and a preparation method thereof. An active metal compound and a promoter metal compound are dissolved in a mixed solution of water and an organic solvent to obtain an impregnation solution, a carrier is impregnated with the impregnation solution, and the impregnated carrier is finally calcined to obtain a catalyst in which at least 90% of the active components are present in a carrier with a thickness of at most 250 μm. The catalyst performs well in the selective hydrogenation of acetylenic compounds.

[0004] CN103769094A discloses an eggshell-type catalyst for selective hydrogenation reaction. The carrier is immersed in aqueous solutions of a reducing agent, an auxiliary agent and an active component respectively. After drying, calcination and reduction, an eggshell-type catalyst with low precious metal loading and low cost is obtained. The catalyst has the characteristics of high activity, good selectivity and stability in the selective hydrogenation reaction of C=C bonds in α,β-unsaturated carbonyl compounds.

[0005] CN111229216A discloses an eggshell-type silver catalyst and its preparation method and application. The invention adopts a chemical energy transfer-deposition method, firstly immerses an active precursor solution and then performs in-situ treatment to obtain an eggshell-type silver catalyst. The eggshell-type silver catalyst is suitable for oxidative dehydrogenation of alcohols to produce aldehydes and epoxidation reactions, especially catalyzing the oxidative dehydrogenation of isopentenol to produce isopentenal.

[0006] Most of the existing technical solutions (such as the above-mentioned CN101730588A, CN103769094A, CN111229216A) use the traditional impregnation method, which has many and complex influencing factors (such as pH value, metal ion concentration, viscosity, drying process, etc.), making it difficult to control parameters such as catalyst shell thickness, active metal loading, and dispersion. At the same time, such methods often use various organic reducing agents, dispersants, and solvents, which are not environmentally friendly and are not easy to scale up for production. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides an ultra-thin eggshell-type highly dispersed catalyst and its preparation method and application. The method starts from regulating the surface properties of the carrier, and uses heat treatment, crystallization, irradiation and other means to treat the alumina precursor mixture of carbon compounds to enrich and improve the types and density of oxygen-containing groups on the surface of the alumina carrier, so that the active metal is distributed in the extremely thin shell region on the surface of the carrier while being highly dispersed, and exhibits excellent performance in the selective hydrogenation catalytic reaction.

[0008] The first aspect of the present invention is to provide an eggshell-shaped catalyst, the catalyst comprising a carrier and an active metal element, wherein the active metal element accounting for 95wt% to 99wt% of the total weight of the active metal element is distributed in a shell within 60μm of the carrier in an eggshell-shaped distribution, with the thickness calculated from the outer surface of the carrier to the center;

[0009] The dispersion degree of the active metal element is 50% to 80%;

[0010] The active metal elements include a main metal element and an optional auxiliary metal element.

[0011] In a preferred embodiment of the present invention, the active metal elements accounting for 95wt% to 99wt% of the total weight of the active metal elements are distributed in the shell of the carrier with a thickness within 50μm, with the thickness calculated from the outer surface of the carrier to the center; and / or,

[0012] In a preferred embodiment of the present invention, the dispersion of the active metal element is 60% to 80%. In a preferred embodiment of the present invention, the average particle size of the active metal is less than 4 nm; and / or, in a preferred embodiment of the present invention, the specific surface area of ​​the catalyst is 20-150 m 2 / g.

[0013] According to the present invention, the ratio of the weight of the main metal element to the weight of the carrier can be selected within a wide range. In a preferred embodiment of the present invention, based on the weight of the main metal element, the ratio of the weight of the main metal element to the weight of the carrier is (0.01-0.5):100.

[0014] According to the present invention, the main metal element can be selected from a wide range. In a preferred embodiment of the present invention, the main metal element is selected from at least one of the metal elements of Group VIIIB, preferably palladium.

[0015] According to the present invention, the ratio of the total weight of the auxiliary metal elements to the weight of the carrier can be selected within a wide range. In a preferred embodiment of the present invention, based on the weight of the auxiliary metal elements, the ratio of the total weight of the auxiliary metal elements to the weight of the carrier is (0-5):100.

[0016] According to the present invention, the auxiliary metal element can be selected from a wide range. In a preferred embodiment of the present invention, the auxiliary metal element is selected from at least one of Group IB, Group IIB, Group IIIA, Group IIIA and Lanthanide metal elements, preferably at least one of silver, indium, gallium, cerium and zinc.

[0017] In a preferred embodiment of the present invention, the catalyst is prepared by the following method: impregnating a solution containing an active metal element source on the carrier, and activating the catalyst in an optional order to obtain the catalyst;

[0018] The carrier is an alumina carrier, and the surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.1-0.9 mmol / m 2 ; wherein the oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 20-150m 2 / g; preferably:

[0019] The content of the hydroxyl group is 4-40 mmol / g; and / or,

[0020] The carboxyl content is 2.5-30 mmol / g; and / or,

[0021] The content of the lactone group is 0.05-20 mmol / g.

[0022] In a preferred embodiment of the present invention, the carrier is prepared by the following method:

[0023] The alumina carrier is obtained by mixing dry materials including an alumina precursor, a forming pore-enlarging agent, and inorganic carbon with a liquid, and kneading, granulating, and surface-modifying the alumina carrier; the inorganic carbon is selected from at least one of charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond;

[0024] The surface modification method is: heat treatment; or, heat treatment and crystallization; or, heat treatment and irradiation; or, irradiation and crystallization;

[0025] The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of air, nitrogen and carbon dioxide, the second atmosphere is selected from water vapor, the volume ratio of the first atmosphere to the second atmosphere is (1-2):1, the heat treatment temperature is 300-1200°C, and the heat treatment time is 1-24h.

[0026] According to the present invention, the crystallization conditions can be selected within a wide range. In a preferred embodiment of the present invention, the crystallization conditions include at least one of the following conditions: 150-250°C, 2-24h, 0.2-10Mpa, the solvent is water, and the pH of the solution used for crystallization is 8-14.

[0027] In a preferred embodiment of the present invention, the irradiation conditions include: the irradiation source is selected from gamma rays, and / or the irradiation dose is 1 to 20 kGy.

[0028] In a preferred embodiment of the present invention, the amount of the inorganic carbon is 1-30 parts by mass relative to 100 parts by mass of the alumina precursor.

[0029] In a preferred embodiment of the present invention, when the inorganic carbon is charcoal, bamboo charcoal, or coconut shell charcoal, the surface modification is performed by heat treatment and crystallization; when the inorganic carbon species is graphene, graphyne, or diamond, the surface modification is performed by heat treatment and irradiation; or, the surface modification is performed by irradiation and crystallization.

[0030] According to the present invention, the alumina precursor can be selected from a wide range. In a preferred embodiment of the present invention, the alumina precursor is selected from at least one of pseudo-boehmite, α-alumina, θ-alumina, γ-alumina, and amorphous alumina, preferably at least one of pseudo-boehmite, α-alumina, and γ-alumina.

[0031] According to the present invention, the molding pore expanding agent can be selected within a wide range. In a preferred embodiment of the present invention, the molding pore expanding agent is at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, starch and at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol, and sesbania powder.

[0032] According to the present invention, the ratio of the mass of the forming pore expanding agent to the total mass of the dry material can be selected within a wide range. In a preferred embodiment of the present invention, the ratio of the mass of the forming pore expanding agent to the total mass of the dry material is (0.5-25):100.

[0033] In a preferred embodiment of the present invention, the liquid is an acidic solution, preferably, the acidic solution is selected from at least one of aqueous solutions of acetic acid, oxalic acid, diacetic acid, maleic acid, citric acid, oxalic acid, formic acid, tartaric acid, nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid, and / or the concentration of the acidic solution is 0.01 to 5 mol / L, preferably 0.2 to 4 mol / L.

[0034] The second aspect of the present invention is to provide a method for preparing the catalyst described in the first aspect, comprising:

[0035] The catalyst is obtained by impregnating a solution containing an active metal element source on the carrier and activating the solution in an optional order; the active metal element source includes a main metal element source and an optional auxiliary metal element source;

[0036] The carrier is an alumina carrier, and the surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.1-0.9 mmol / m 2 ;

[0037] The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 20-150 m 2 / g; preferably:

[0038] The content of the hydroxyl group is 4-40 mmol / g; and / or,

[0039] The carboxyl content is 2.5-30 mmol / g; and / or,

[0040] The content of the lactone group is 0.05-20 mmol / g.

[0041] The preferred preparation method of the carrier in the present invention is as described in the first aspect and will not be repeated here.

[0042] According to the present invention, the main metal element source can be selected within a wide range. In a preferred embodiment of the present invention, the main metal element source is selected from at least one of soluble compounds containing the main metal element, preferably at least one of water-soluble palladium compounds; more preferably at least one of palladium nitrate, palladium chloride, sodium chloropalladate, palladium oxalate, and palladium citrate.

[0043] Preferably, the weight ratio of the palladium compound content, calculated as metal element, to the carrier is (0.01-0.5):100, preferably (0.02-0.45):100.

[0044] According to the present invention, the auxiliary metal element source can be selected in a wide range. In a preferred embodiment of the present invention, the auxiliary metal element source is selected from at least one of soluble compounds containing auxiliary metal elements, preferably a water-soluble auxiliary metal element salt compound. As an example, the auxiliary metal compound is at least one of soluble salt compounds of silver, indium, gallium, cerium, zinc, etc.; the content of the auxiliary metal compound, calculated as metal element, is in a weight ratio of (0 to 5):100 to the carrier; preferably (0.02 to 4):100;

[0045] In a preferred embodiment of the present invention, the activation method includes a calcination stage, or an irradiation stage, or an optional sequential calcination stage and an irradiation stage. Preferably,

[0046] The calcination conditions include: 150-750°C, and / or, 4-20 hours, and / or, the atmosphere is at least one of air, nitrogen, hydrogen, and argon. The calcination conditions are preferably 180-725°C, 6-18 hours; the atmosphere is at least one of air, nitrogen, hydrogen, and argon, preferably at least one of air, nitrogen, and hydrogen.

[0047] In a preferred embodiment of the present invention, the irradiation conditions include: the irradiation source is selected from gamma rays, and / or the irradiation dose is 1 to 20 kGy, preferably 4 to 18 kGy.

[0048] The impregnation solution used is a palladium compound, or an aqueous solution of an auxiliary metal compound, or a mixture of the two aqueous solutions.

[0049] According to the present invention, when there are two or more impregnation solutions, the impregnation can be performed in steps or simultaneously. When the impregnation is performed in steps, each impregnation needs to be dried before the next impregnation. The calcination and activation can be performed in steps, or the calcination and activation can be performed at one time after all components are loaded.

[0050] According to the present invention, the number of impregnations is one or more, and the activation is optionally carried out before the impregnation, after the impregnation, or in the interval between multiple impregnations; preferably, when the activation comprises multiple stages, some stages of the activation are optionally carried out before the impregnation, after the impregnation, or in the interval between multiple impregnations.

[0051] The third aspect of the present invention is to provide an application of the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect in the field of catalytic hydrogenation;

[0052] Preferably, the invention is used in the preparation of ethylene by catalytic hydrogenation of acetylene.

[0053] Compared with the prior art, the advantages of the present invention are:

[0054] (1) The catalyst of the present invention: 95 wt% to 99 wt% of the total weight of the active metal elements are distributed in the shell layer of the carrier with a thickness of less than 60 μm, which has a thinner shell layer than the conventional eggshell catalyst, and is more conducive to surface fast reaction and diffusion-controlled catalytic reaction;

[0055] (2) The catalyst of the present invention has a dispersion of active metal elements of 50% to 80%, which is higher than that of conventional eggshell catalysts, and has a higher atomic utilization rate of active metals, which can significantly reduce the catalyst cost;

[0056] (3) The present invention prepares the catalyst by using a specific alumina carrier with a high content and density of oxygen-containing groups. Not only does it have lower requirements on the impregnation conditions, but the rich oxygen-containing group types and high density on the surface of the alumina carrier can distribute the active metal in an extremely thin shell area on the surface of the carrier while weakening its growth, agglomeration or aggregation tendency, thereby presenting a highly dispersed state, and the regulation of the catalyst is more precise and accurate.

[0057] (4) The catalyst of the present invention exhibits excellent performance in the selective hydrogenation catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 SEM results of active metal palladium of catalyst C1 in Example 1.

[0059] Figure 2 SEM results of active metal palladium of catalyst D1 in Comparative Example 1. DETAILED DESCRIPTION

[0060] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0061] Example 1

[0062] Take 200g pseudo-boehmite powder, 6g methyl cellulose, 6g polypropylene glycol, and 5g charcoal and mix them evenly. Add 20ml of a mixed solution of 0.8mol / L nitric acid and 0.5mol / L citric acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm spherical particles, dry at 110℃ for 4h, and then heat treat at 1080℃ in air and water vapor (volume ratio 1.5:1) for 2h to obtain alumina carrier A1. Take 50g of A1 and immerse it in 60ml of a solution containing 0.034g palladium chloride for 3h, dry at 110℃ for 4h, and calcine in a hydrogen atmosphere at 400℃ for 12h to obtain catalyst C1.

[0063] Example 2

[0064] Take 100g of α-alumina and 50g of amorphous alumina, 6g of methyl cellulose, 6g of polypropylene glycol, and 7g of diamond and mix them evenly. Add 40ml of a mixed solution of 2mol / L oxalic acid and 1mol / L acetic acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm diameter spherical particles, dry at 110℃ for 4h, then heat treat at 350℃ for 12h with nitrogen, carbon dioxide and water vapor (volume ratio 1:1:1), and then crystallize in an aqueous solution at 340℃, 9MPa, and pH 13 for 3h to obtain alumina carrier A2. Take 50g of A2 and immerse it in 60ml of a solution containing 0.034g of palladium chloride for 3h, dry at 110℃ for 4h, and calcine at 700℃ in air atmosphere for 5h to obtain catalyst C2.

[0065] Example 3

[0066] Take 100g of α-alumina and 50g of θ-alumina, 5g of methyl cellulose, 5g of starch, 5g of polypropylene glycol, 5g of sesbania powder, 5g of bamboo charcoal and 5g of coconut shell charcoal, and mix them evenly. Add 45ml of 1.5mol / L sulfuric acid solution to the mixed powder, and then fully knead, extrude, shape and pelletize it to obtain 3mm spherical particles, dry at 110℃ for 4h, crystallize at 150℃, 0.3MPa, pH 8 aqueous solution for 12h, and then heat treat with carbon dioxide and water vapor (volume ratio 1:1) at 350℃ for 12h to obtain alumina carrier A3. Take 50g of A3 and immerse it in 60ml of solution containing 0.037g of palladium oxalate for 3h, dry at 110℃ for 4h, calcine at 150℃ in air atmosphere for 23h, and irradiate with γ rays for 10kGy to obtain catalyst C3.

[0067] Example 4

[0068] Take 100g of α-alumina and 50g of θ-alumina, 5g of methylcellulose, 5g of starch, 5g of polypropylene glycol, 5g of sesbania powder, 3g of graphene and 3g of graphyne, and mix them evenly. Add 30mL of a mixed solution of 0.5mol / L hydrochloric acid and 0.2mol / L hypochlorous acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm spherical particles, dry at 110℃ for 4h, and then crystallize at 245℃, 5MPa, pH 12 in an aqueous solution for 22h, and then irradiate with γ rays for 3kGy to obtain alumina carrier A4. Take 50g of A4 and immerse it in 60ml of a solution containing 0.037g of palladium oxalate for 3h, and irradiate it with γ rays for 5kGy to obtain catalyst C4.

[0069] Example 5

[0070] Take 80g of amorphous alumina and 40g of pseudo-boehmite, 10g of starch, 10g of sesbania powder, and 15g of diamond, and mix them evenly. Add 25mL of 0.5mol / L nitric acid solution to the mixed powder, and then fully knead, extrude, shape, and pelletize it to obtain 3mm spherical particles, dry at 110℃ for 4h, irradiate with γ-rays for 18kGy, and then heat-treat with air, carbon dioxide and water vapor (volume ratio 1:1:1) at 650℃ for 6h to obtain alumina carrier A5. Take 50g of A5 and immerse it in 60ml of a mixed solution containing 0.108g of palladium nitrate and 0.039g of silver nitrate for 3h, and irradiate with γ-rays for 5kGy to obtain catalyst C5.

[0071] Example 6

[0072] Take 80g of amorphous alumina and 40g of pseudo-boehmite, 10g of starch, 10g of sesbania powder, and 15g of diamond, and mix them evenly. Add 50mL of 3.5mol / L phosphoric acid solution to the mixed powder, and then fully knead, extrude, shape, and pelletize it to obtain 3mm spherical particles, dry at 110℃ for 4h, and then heat treat with air and water vapor (volume ratio 1:1) at 650℃ for 6h to obtain alumina carrier A6. Take 50g of A6 and immerse it in 60ml of 0.108g of palladium nitrate solution for 3h, dry it at 110℃ for 4h, and then immerse it in 0.039g of silver nitrate solution for 3h, and irradiate it with γ rays for 2kGy to obtain catalyst C6.

[0073] Example 7

[0074] Take 80g of amorphous alumina and 40g of pseudo-boehmite, 10g of starch, 10g of sesbania powder, 4g of coconut shell charcoal, and 6g of bamboo charcoal and mix them evenly. Add 50mL of a mixed solution of 1.5mol / L formic acid, 1.5mol of maleic acid, and 0.5mol / L of diacetic acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm diameter spherical particles, dry at 110°C for 4h, irradiate with 10kGy for 4h, and then crystallize in an aqueous solution at 190°C, 2MPa, and pH 10 for 4h to obtain an alumina carrier A7. Then 50 g of A7 was immersed in 60 ml of 4.34 g of zinc nitrate solution for 3 h, dried at 110°C for 4 h, immersed in 0.344 g of sodium chloropalladate solution for 3 h, dried at 110°C for 4 h, calcined in a hydrogen atmosphere at 500°C for 8 h, immersed in 1.55 g of cerium nitrate solution, and irradiated with γ-rays for 10 kGy to obtain catalyst C7.

[0075] Example 8

[0076] Take 80g of amorphous alumina and 40g of pseudo-boehmite, 10g of starch, 10g of sesbania powder, 4g of graphene, and 6g of diamond, and mix them evenly. Add 50mL of a mixed solution of 1.0mol / L oxalic acid and 0.5mol / L nitric acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm spherical particles, which are irradiated with γ rays for 15kGy, and then heat-treated at 650℃ for 8h in carbon dioxide and water vapor (volume ratio 1:1) to obtain alumina carrier A8. Take 50g of A8 and immerse it in 60ml of zinc sulfate solution containing 6.75g for 3h, dry it at 110℃ for 4h, and calcine it at 400℃ in air and nitrogen (volume ratio 1:1) for 4h, and then immerse it in a solution containing 0.344g of sodium chloropalladate for 3h, and calcine it at 500℃ in hydrogen atmosphere for 6h to obtain catalyst C8.

[0077] Comparative Example 1

[0078] Take 200g pseudo-boehmite powder, 6g methyl cellulose, 6g polypropylene glycol, 3g charcoal, 3g bamboo charcoal, 3g coconut shell charcoal, 3g graphene, 3g graphyne, and 3g diamond, and mix them evenly. Add 20ml of a mixed solution of 0.8mol / L nitric acid and 0.5mol / L citric acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm diameter spherical particles, dry at 110℃ for 4h, and then heat treat at 1080℃ in air for 2h to obtain alumina carrier B1. Take 50g of B1 and immerse it in 60ml of a solution containing 0.034g palladium chloride for 3h, dry at 110℃ for 4h, and calcine in a hydrogen atmosphere at 400℃ for 12h to obtain catalyst D1.

[0079] Comparative Example 2

[0080] Take 100g of α-alumina and 50g of amorphous alumina, 6g of methyl cellulose, and 6g of polypropylene glycol and mix them evenly. Add 40ml of a mixed solution of 2mol / L oxalic acid and 1mol / L acetic acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm spherical particles, dry at 110℃ for 4h, then heat treat with nitrogen, carbon dioxide and water vapor (volume ratio 1:1:1) at 350℃ for 12h, and then crystallize in an aqueous solution at 340℃, 9MPa, and pH 13 for 3h to obtain alumina carrier B2. Take 50g of A2 and immerse it in 60ml of a solution containing 0.034g of palladium chloride for 3h, dry at 110℃ for 4h, and calcine at 700℃ in air atmosphere for 5h to obtain catalyst D2.

[0081] Comparative Example 3

[0082] Take 100g of α-alumina and 50g of θ-alumina, 5g of methylcellulose, 5g of starch, 5g of polypropylene glycol, and 5g of sesbania powder and mix them evenly. Add 30mL of a mixed solution of 0.5mol / L hydrochloric acid and 0.2mol / L hypochlorous acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm spherical particles, dry at 110℃ for 4h, and then crystallize at 245℃, 5MPa, pH 12 in an aqueous solution for 22h, and then irradiate with γ rays for 3kGy to obtain alumina carrier B3. Take 50g of B3 and immerse it in 60ml of a solution containing 0.037g of palladium oxalate for 3h, and irradiate it with γ rays for 5kGy to obtain catalyst D3.

[0083] Comparative Example 4

[0084] Take 80g of amorphous alumina and 40g of pseudo-boehmite, 10g of starch, and 10g of sesbania powder and mix them evenly. Add 25mL of 0.5mol / L nitric acid solution to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm spherical particles, dry at 110℃ for 4h, irradiate with γ-rays for 18kGy, and then heat-treat with air, carbon dioxide and water vapor (volume ratio 1:1:1) at 650℃ for 6h to obtain alumina carrier B4. Take 50g of B4 and immerse it in 60ml of a mixed solution containing 0.108g of palladium nitrate and 0.039g of silver nitrate for 3h, and irradiate with γ-rays for 5kGy to obtain catalyst D4.

[0085] Comparative Example 5

[0086] Take 80g of amorphous alumina and 40g of pseudo-boehmite, 10g of starch, and 10g of sesbania powder and mix them evenly. Add 50mL of 3.5mol / L phosphoric acid solution to the mixed powder, and then fully knead, extrude, shape, and pelletize it to obtain 3mm spherical particles, dry at 110℃ for 4h, and then heat treat with air and water vapor (volume ratio 1:1) at 650℃ for 6h to obtain alumina carrier B5. Take 50g of B5 and immerse it in 60ml of 0.108g of palladium nitrate solution for 3h, dry it at 110℃ for 4h, and then immerse it in 0.039g of silver nitrate solution for 3h, and irradiate it with γ rays for 2kGy to obtain catalyst D5.

[0087] Comparative Example 6

[0088] Take 80g of amorphous alumina, 40g of pseudo-boehmite, 10g of starch, and 10g of sesbania powder and mix them evenly. Add 50mL of a mixed solution of 1.5mol / L formic acid, 1.5mol of maleic acid, and 0.5mol / L of diacetic acid to the mixed powder, and then fully knead, extrude, shape, and pelletize to obtain 3mm diameter spherical particles, dry at 110°C for 4h, irradiate with 10kGy for 4h, and then crystallize in an aqueous solution at 190°C, 2MPa, and pH 10 for 4h to obtain alumina carrier B6. Then 50 g of B6 was immersed in 60 ml of 4.34 g of zinc nitrate solution for 3 h, dried at 110°C for 4 h, immersed in 0.344 g of sodium chloropalladate solution for 3 h, dried at 110°C for 4 h, calcined in a hydrogen atmosphere at 500°C for 8 h, immersed in 1.55 g of cerium nitrate solution, and irradiated with γ-rays for 10 kGy to obtain catalyst D6.

[0089] Test example

[0090] Determination of specific surface area of ​​carrier physical properties: nitrogen physical adsorption BET method was used for measurement.

[0091] Determination of the density of oxygen-containing groups in the carrier: The Boehm chemical method was used to determine the nature and quantity of oxygen-containing groups in the carrier. Three 1g carrier samples were weighed and placed in 50ml of 0.05mol / L NaHCO 3 、Na 2 CO 3 Soak in NaOH solution for 24 hours. Titrate 10 ml of the soaking solution with 0.06 mol / L hydrochloric acid. Titrate each sample three times, take the arithmetic mean, calculate the number of various oxygen-containing groups on the carrier surface based on the consumption of alkali, and obtain the oxygen-containing group density based on the carrier specific surface data.

[0092] Determination of active metal distribution on catalyst surface: The catalyst sample particles were cut in half, and the distribution of active elements on the particle cross section was analyzed using a JSM-7900F scanning electron microscope with an energy dispersive spectrometer EDX element analysis accessory. The shell thickness L corresponding to the active metal content exceeding 95% in the shell range from the outside to the inside of the cross section where the active metal content is less than 0.01% was calculated (three different positions were measured on each cross section and the average value was taken).

[0093] Determination of palladium content in the catalyst: The conventional ICP-MS method was used to detect the content of palladium metal in the catalyst.

[0094] Determination of the dispersion of active metals in the catalyst: Use a Chemisorb 2920 chemical adsorption instrument to weigh 0.1 g of the catalyst sample, reduce it with hydrogen at 160°C for 30 min, purge it with nitrogen for 10 min, then cool it to 40°C, perform CO pulse adsorption until adsorption saturation, and calculate the dispersion of the active metal based on the adsorption amount and palladium content.

[0095] Determination of the particle size distribution of active metals in catalysts: Cut the catalyst sample particles with a surface area of ​​about 0.5 mm, grind them, and reduce them in hydrogen at 160°C for 1 hour. Then add the powder sample to a solution with a volume ratio of water to ethanol of 4:1, disperse it by ultrasonic, and then use a dropper to drop 4 to 6 drops of the dispersed solution onto a copper mesh. After drying with an infrared lamp for 15 minutes, transfer it directly to an electron microscope. Collect 4 images for each sample and calculate the particle size of no less than 200 particles in total.

[0096] Catalytic performance test: 10 ml of catalyst was loaded into a tubular reactor, and hydrogen was introduced after nitrogen replacement at 160 ° C for 3 h; after natural cooling to room temperature, nitrogen was purged and replaced at a space velocity of 20000 h -1 and a carbon two reaction material (material 1) under a pressure of 2 MPa to perform a performance test (test 1); repeat the above steps and conditions to perform a performance test (test 2) in a carbon two reaction material (material 2)

[0097] Material 1 consists of: 1000 ppm acetylene, 800 ppm carbon monoxide, 13% hydrogen, 12% ethane, 1% methane, 20% propylene, 0.3% propadiene, 0.2% propyne, 0.9% propane, and the remainder is ethylene.

[0098] Material 2 consists of 1000 ppm acetylene, 900 ppm carbon monoxide, 26% hydrogen, 14% ethane, 3% methane, and the remainder is ethylene.

[0099] The lowest temperature and ethylene selectivity corresponding to the acetylene concentration of 0 ppm in the outlet gas were investigated.

[0100] The ethylene selectivity is calculated as follows:

[0101] Ethylene selectivity = [(ethylene content at outlet - ethylene content at inlet) / (acetylene content at inlet)] × 100%

[0102] Table 1. Measurement results of oxygen-containing groups on alumina carriers of Examples and Comparative Examples

[0103]

[0104]

[0105] Table 2 Physical and chemical properties characterization test results of catalysts in Examples and Comparative Examples

[0106]

[0107]

[0108] Table 3 Catalytic performance evaluation results of the catalysts of the examples and comparative examples

[0109]

[0110] As can be seen from Table 1, the carrier modification method of the present invention can significantly increase the content and density of various oxygen-containing groups on the surface of the alumina carrier. Figure 1 and Figure 2 From the comparison and combination of Table 2, it can be seen that the active metals of the example catalysts are significantly different from those of the comparative example catalysts. They are all enriched in an extremely thin shell layer (less than 60 μm), and the dispersion is above 55%. The average particle size is less than 4 nm. This is mainly due to the high density and rich variety of oxygen-containing groups on the surface of the example carrier.

[0111] The results in Table 3 show that, under the same condition of reaching an acetylene outlet concentration of 0 ppm, that is, when the acetylene conversion rate is 100%, the temperature required by the catalyst of the embodiment is lower than that of the corresponding comparative catalyst, indicating that the activity of the catalyst of the embodiment is better. And when the acetylene conversion rate is 100%, the selectivity of the catalyst of the embodiment is also better than that of the corresponding comparative catalyst. Therefore, the performance of the catalyst of the embodiment is better than that of the comparative catalyst, and an unexpected technical effect is achieved.

[0112] In two typical C2 selective hydrogenation reactions (Table 3), the activity and selectivity of the catalyst of the examples are significantly better than those of the catalyst of the comparative examples. This can be attributed to the fact that the C2 selective hydrogenation reaction is a surface fast reaction and diffusion controlled catalytic reaction. When the active metal distribution of the catalyst is more concentrated in the outer layer of the catalyst and the degree of dispersion is higher (atomic utilization), its activity is better, and the desorption of ethylene is easier, the diffusion path from the catalyst surface to the gas phase is shorter, and the probability of over-hydrogenation is lower, so the selectivity of the catalyst is also higher.

[0113] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0114] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0115] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0116] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0117] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0118] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. An eggshell-shaped catalyst, comprising a carrier and an active metal element, wherein the active metal element accounting for 95 wt% to 99 wt% of the total weight of the active metal element is distributed in a shell within 60 μm of the carrier in an eggshell-shaped distribution, with the thickness calculated from the outer surface of the carrier to the center; The dispersion degree of the active metal element is 50% to 80%; The active metal elements include a main metal element and an optional auxiliary metal element.

2. The catalyst according to claim 1, characterized in that: The thickness is calculated from the outer surface of the carrier to the center, and 95wt% to 99wt% of the total weight of the active metal elements are distributed in the shell of the carrier with a thickness of less than 50μm; and / or, The dispersion degree of the active metal element is 60% to 80%; and / or, The average particle size of the active metal is less than 4 nm; and / or, The specific surface area of ​​the catalyst is 20-150m 2 / g.

3. The catalyst according to claim 1, characterized in that: Based on the weight of the main metal element, the ratio of the weight of the main metal element to the weight of the carrier is (0.01-0.5):100; and / or, The main metal element is selected from at least one of the metal elements of Group VIIIB, preferably palladium; and / or, Based on the weight of the auxiliary metal elements, the ratio of the total weight of the auxiliary metal elements to the weight of the carrier is (0-5):100; and / or, The auxiliary metal element is selected from at least one of Group IB, Group IIB, Group IIIA, Group IIIB, and lanthanide metal elements, preferably at least one of silver, indium, gallium, cerium, and zinc.

4. The catalyst according to any one of claims 1 to 3, characterized in that: The catalyst is prepared by the following method: impregnating a solution containing an active metal element source on the carrier, and activating the catalyst in an optional order to obtain the catalyst; The carrier is an alumina carrier, and the surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.1-0.9 mmol / m 2 ; The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 20-150 m 2 / g; preferably: The content of the hydroxyl group is 4-40 mmol / g; and / or, The carboxyl content is 2.5-30 mmol / g; and / or, The content of the lactone group is 0.05-20 mmol / g.

5. The catalyst according to claim 4, characterized in that The carrier is prepared by the following method: The alumina carrier is obtained by mixing dry materials including an alumina precursor, a forming pore-enlarging agent, and inorganic carbon with a liquid, and kneading, granulating, and surface-modifying the alumina carrier; the inorganic carbon is selected from at least one of charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; The surface modification method is: heat treatment; or, heat treatment and crystallization; or, heat treatment and irradiation; or, irradiation and crystallization; The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of air, nitrogen and carbon dioxide, the second atmosphere is selected from water vapor, the volume ratio of the first atmosphere to the second atmosphere is (1-2):1, the heat treatment temperature is 300-1200°C, and the heat treatment time is 1-24h.

6. The catalyst according to claim 5, characterized in that: The crystallization conditions include at least one of the following conditions: 150-250°C, 2-24h, 0.2-10Mpa, the solvent is water, and the pH of the solution used for crystallization is 8-14; and / or, The irradiation conditions include: the ray source is selected from gamma rays, and / or the irradiation dose is 1 to 20 kGy.

7. The catalyst according to claim 5, characterized in that: In parts by mass, the amount of the inorganic carbon is 1-30 parts relative to 100 parts of the alumina precursor; and / or, When the inorganic carbon is charcoal, bamboo charcoal, or coconut shell charcoal, the surface modification is performed by heat treatment and crystallization; when the inorganic carbon species is graphene, graphyne, or diamond, the surface modification is performed by heat treatment and irradiation; or, the surface modification is performed by irradiation and crystallization.

8. The catalyst according to claim 5, characterized in that: The alumina precursor is selected from at least one of pseudo-boehmite, α-alumina, θ-alumina, γ-alumina, and amorphous alumina; and / or, The forming pore-enlarging agent is at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, starch and at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol, and sesbania powder; and / or, The ratio of the mass of the forming pore-enlarging agent to the total mass of the dry material is (0.5-25):100; and / or, The liquid is an acidic solution. Preferably, the acidic solution is selected from at least one of aqueous solutions of acetic acid, oxalic acid, diacetic acid, maleic acid, citric acid, oxalic acid, formic acid, tartaric acid, nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid, and / or the concentration of the acidic solution is 0.01 to 5 mol / L.

9. A method for preparing the catalyst according to any one of claims 1 to 8, comprising: impregnating a solution containing an active metal element source on the support and activating the support in an optional sequence to obtain the catalyst; The active metal element source includes a main metal element source and an optional auxiliary metal element source; The carrier is an alumina carrier, and the surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.1-0.9 mmol / m 2 ; The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 20-150 m 2 / g; preferably: The content of the hydroxyl group is 4-40 mmol / g; and / or, The carboxyl content is 2.5-30 mmol / g; and / or, The content of the lactone group is 0.05-20 mmol / g.

10. The preparation method according to claim 9, characterized in that: The main metal element source is selected from at least one of soluble compounds containing the main metal element, preferably at least one of water-soluble palladium compounds; more preferably, the palladium compound is at least one of palladium nitrate, palladium chloride, sodium chloropalladate, palladium oxalate, and palladium citrate, and / or the content of the palladium compound, calculated as the metal element, is in a weight ratio of (0.01-0.5) to the carrier: 100; and / or, The auxiliary metal element source is selected from at least one of soluble compounds containing auxiliary metal elements, preferably a water-soluble auxiliary metal element salt compound; and / or, The weight ratio of the compound containing the auxiliary metal element to the carrier is (0-5):100, calculated as the metal element.

11. The preparation method according to claim 9 or 10, characterized in that: The activation method includes a calcination stage, an irradiation stage, or an optional sequential calcination stage and an irradiation stage. Preferably, The calcination conditions include: 150-750° C., and / or, 4-20 hours, and / or, the atmosphere is at least one of air, nitrogen, hydrogen, and argon; and / or, The irradiation conditions include: the irradiation source is selected from gamma rays, and / or the irradiation dose is 1 to 20 kGy; and / or, The number of impregnations is one or more, and the activation is optionally performed before, after, or in the interval between multiple impregnations; preferably, when the activation comprises multiple stages, some stages of the activation are optionally performed before, after, or in the interval between multiple impregnations.

12. Use of the catalyst according to any one of claims 1 to 8 or the catalyst prepared by the preparation method according to any one of claims 9 to 11 in the field of catalytic hydrogenation; Preferably, the invention is used in the catalytic hydrogenation of acetylene to produce ethylene.

Citation Information

Patent Citations

  • Catalyst for the selective hydrogenation of acetylenic hydrocarbons and method for producing said catalyst

    CN101730588A

  • Eggshell type catalyst for selective hydrogenation reaction as well as preparation method and application thereof

    CN103769094A

  • Eggshell type silver catalyst and preparation method and application thereof

    CN111229216A

  • Preparation method of eggshell hydrogenation catalyst

    CN103100391A

  • Preparation method of boron-containing hydrogenation and demetalization catalyst

    CN106140122A